2012
DOI: 10.1371/journal.pone.0043214
|View full text |Cite
|
Sign up to set email alerts
|

Does Pet Ownership in Infancy Lead to Asthma or Allergy at School Age? Pooled Analysis of Individual Participant Data from 11 European Birth Cohorts

Abstract: ObjectiveTo examine the associations between pet keeping in early childhood and asthma and allergies in children aged 6–10 years.DesignPooled analysis of individual participant data of 11 prospective European birth cohorts that recruited a total of over 22,000 children in the 1990s.Exposure definitionOwnership of only cats, dogs, birds, rodents, or cats/dogs combined during the first 2 years of life.Outcome definitionCurrent asthma (primary outcome), allergic asthma, allergic rhinitis and allergic sensitizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
110
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(131 citation statements)
references
References 41 publications
(30 reference statements)
12
110
1
2
Order By: Relevance
“…We reported previously that family ownership of domestic pets during early life, including during the pre-natal period, was associated with lower odds of atopic asthma by mid-childhood compared with no pet ownership [7], confirming findings from previous studies [810]. Conversely, we also found that pet ownership, particularly of rabbits and rodents, tended to be associated with higher odds of non-atopic asthma.…”
Section: Introductionsupporting
confidence: 90%
“…We reported previously that family ownership of domestic pets during early life, including during the pre-natal period, was associated with lower odds of atopic asthma by mid-childhood compared with no pet ownership [7], confirming findings from previous studies [810]. Conversely, we also found that pet ownership, particularly of rabbits and rodents, tended to be associated with higher odds of non-atopic asthma.…”
Section: Introductionsupporting
confidence: 90%
“…Specifically, while some studies have shown that exposure to pets within the first months or year of life increases the risk of subsequent allergic diseases, other studies have reported an inverse or no relationship between exposure to pets and risk of allergies (Chen et al, 2008;Wegienka et al, 2011;Lødrup Carlsen et al, 2012). In the current study, we found no significant correlation between pet ownership and AR severity.…”
Section: Discussionmentioning
confidence: 99%
“…106 Tener un gato pareció ser un factor protector. 107 Tampoco damos una recomendación para reducir la exposición a ácaros de polvo casero como medida de prevención primaria para asma.…”
Section: Control Del Medio Ambienteunclassified